Characterization of a herpes simplex virus type 2 75,000-molecular-weight glycoprotein antigenically related to herpes simplex virus type 1 glycoprotein C. - Zezulak, K M (1983)
Evidence is presented that the herpes simplex virus type 2 glycoprotein previously designated gF is antigenically related to herpes simplex virus type 1 gC (gC-1). An antiserum prepared against type 1 virion envelope proteins immunoprecipitated gF of type 2 (gF-2), and competition experiments revealed that the anti-gC-1 component of the antiserum was responsible for the anti-gF-2 cross-reactivity. An antiserum prepared against fully denatured purified gF-2, however, and three anti-gF-2 monoclonal antibodies failed to precipitate any type 1 antigen, indicating that the extent of cross-reactivity between gC-1 and gF-2 may be limited. Several aspects of gF-2 synthesis and processing were investigated. Use of the enzymes endo-beta-N-acetylglucosaminidase H and alpha-D-N-acetylgalactosaminyl oligosaccharidase revealed that the fully processed form of gF-2 (about 75,000 [75K] apparent molecular weight) had both complex-type N-linked and O-linked oligosaccharides, whereas newly synthesized forms (67K and 69K) had only high-mannose N-linked oligosaccharides. These last two forms were both reduced in size to 54K by treatment with endo-beta-N-acetylglucosaminidase H and therefore appear to differ only in the number of N-linked chains. Neutralization tests and radioiodination experiments revealed that gF-2 is exposed on the surfaces of virions and that the 75K form of gF-2 is exposed on cell surfaces. The similarities and differences of gF-2 and gC-1 are discussed in light of recent mapping results which suggest collinearity of their respective genes.